Associations between blood pressure and economic modernization among adults on Rarotonga, the Cook Islands - Ulijaszek, Stanley J.; Kozieł, Sławomir (Polskie Towarzystwo Antropologiczne, 2003)
Populations in the Pacific islands undergoing economic modernization have experienced a steady rise in the prevalance of hypertension across the second part of the twentieth century. In this analysis, a comparison is made between blood pressure of the Rarotonga, Cook Islands, population in 1996 with values obtained for this population in 1964. In addition, the extent to which education and occupation, as markers of modernization, associate with blood pressure and island of origin is examined, taking into account the use of anti-hypertensive drugs by a subset of the sample. For the males, mean blood pressure shows no difference between 1964 and 1996; for the females, the characteristic increase in blood pressure across the age groups is not statistically significant in the 196 study population. This might be due to the much more extensive use of anti-hypertension medication in the 1996 sample. Island of origin is a significant predictor of blood pressure irrespective of occupation, use of anti-hypertension medication, age and body mass index. Females born on Rarotonga had higher systolic blood pressure, which was also associated with education level, than those born on other Cook Islands. Males born on Rarotonga had significantly higher diastolic blood pressure than males born elsewhere in the Cook Islands.
Keywords: blood pressure; modernization; economic status; BMI; Pacific Islands